Fabrication of Carbon Paste Electrode Modified with Bentonite Nanoparticles and Titanium Dioxide Nanoparticles for Analysis of Methyl Parabens by Cyclic Voltammetry - Hizbullah, Ahmad Jihad; Setiarso, Pirim (Jurnal Pijar Mipa, 2024)
Cosmetics are products of several substances or ingredients with a predetermined time limit. Efforts to extend the time limit of cosmetic use are made by adding preservatives. One preservative that is often used is methylparaben. Methylparaben has been tested using spectrophotometry, voltammetry, and HPLC. In this study, electrode modification was carried out in the voltammetry test to obtain a low detection limit. The purpose of this study was to determine the effect of the working electrode composition of carbon paste, bentonite nanoparticles, titanium dioxide nanoparticles, and paraffin on the best response in the analysis of methylparaben by cyclic voltammetry, knowing the optimum measurement conditions of pH with the best electrode composition in the analysis of methylparaben by cyclic voltammetry. FTIR characterized bentonite nanoparticles to determine vibrations and functional groups, and XRD was performed to determine the phase and particle size. The electrode was made from a mixture of carbon, bentonite nanoparticles, titanium dioxide nanoparticles, and paraffin. The best electrode composition was added with titanium dioxide nanoparticles to obtain a higher peak current. XRD characterization of bentonite nanoparticles showed an average particle size of 43.8155 nm. The result of determining the best electrode composition is 3:2:3:2 with an anodic peak current of 9.6.10-4 A. The best methylparaben measurement at pH seven solution conditions. The latest research shows that carbon paste electrodes modified with bentonite and titanium dioxide nanoparticles can be used for methylparaben analysis.